Formulation and in vitro characterization of raloxifene nanoemulgel for improved skin permeation - Chatterjee, Bappaditya; Mohammed Hasan, Ali Ebrahim (2018)
Raloxifene, an estrogen receptor modulator, has poor bioavailability due to extensive metabolism and poor solubility. The present work aimed to enhance skin permeation of raloxifene for systematic delivery. Raloxifene nanoemulsion has been developed using various combination of sunflower oil and tween 20- transcutol (surfactant-co-surfactant) followed by the in-vitro characterizations (pH, zeta potential, globule size, thermodynamic stability). Optimized nanoemulsion was converted to nanoemulgel by incorporating carbopol 940 (3% (w/v), pH 6.5) followed by rheology. spreadability, drug loading, toxicity, and ex-vivo permeation studies. Selected formulations resulted in 3.80-3.93 (pH), 24.98-33.8 mV (zeta potential) and 153.10-208.20 nm (globule size) with polydispersity index (<0.259). Developed gel has shown viscoelastic behaviour with acceptable viscosity and spreadability. Drug loading in selected gel, were above 91.41%. Ex-vivo permeation study through rat skin showed significantly higher (>2.5 times) permeation of raloxifene compared to normal gel and solution. FTiR and DSC study revealed alteration of skin fluidity that promotes drug permeation. Nanoemulgel could be a better alternative to deliver raloxifene directly to the circulation through skin due to its nanoscaled size, presence of surfactant and enhanced retention of skin.